Analysis of Factors Affecting Capital Structure with Profitability as a Moderating Variable in Consumer Non-Cyclicals Sector Companies - Prayogo, Richard Febrianto; Halawa, Yohanes Frans; Sho, Nelly (Universitas Muhammadiyah Pontianak, 2025)
This study investigates the effect of liquidity, sales growth, firm size, activity ratio, and business risk on capital structure, moderated by profitability. A sample of 60 consumer non-cyclicals companies listed on the Indonesia Stock Exchange (IDX) during 2021–2023 was selected using purposive sampling. Data were analyzed using multiple linear regression. The results show that liquidity, firm size, and activity ratio significantly influence capital structure, while sales growth and business risk do not. Profitability moderates the relationship between all variables and capital structure, except business risk. These findings offer insights for investors and corporate financial decision-makers.